Solusi Permasalahan Pemegangan Cash Holding Jangka Panjang - Fildza Aqilla Nur’aini; Shinta Permata Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The study aims to investigate and test the effect of Cash Holding on Profitability, Leverage, Growth Opportunity, and Capital Expenditure. The population of this study is Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. The study uses a quantitative appoarch annual reports accessed from the official Indonesia Stock Exchange website. The sampling technique used purposive sampling, resulting in 306 observation meeting the research criteria. The analytical method used is multiple linear regression analysis with the assistance of Stata MP 17 software. This study is expected to provide empirical evidence regarding the effect of Profitability, Leverage, Growth Opportunity, and Capital Expenditure on Cash Holding and contribute to the development of literature in the field of corporate finance.